SYNTHESIS, STRUCTURE AND ANTI-RADICAL ACTIVITY OF 6-METHYL-4-OXO-4Н-CHROMEN-3-ACYLHYDRAZONES - Nurkenov О. A.; Ibraev M.K.; Seilkhanov T.M.; Shulgau Z.T.; Fazylov S.D.; Takibayeva A.T. (Academic Scientific Journal of Chemistry, 2019)
This paper demonstrates data on synthesis of 6-methyl-4-oxo-4H-chromen-3-acylhydrazones with condensation of substituted 3-formylchromones and acylhydrazides. It is testifed to the fact that 4-oxo-4H-chromen3-carboxaldehyde with hydrazides of isonicotinic and о- and n-hydroxybenzoic acids in isopropanol at boiling a reaction mixture for 2 h lead to the relevant chromen-containing hydrazones. Structures of the synthesized compounds were investigated with methods of 1 Н and 13С NMR spectroscopy, and data on two-dimensional (1 H-1 H) COSY and (1 H-13C) HMQC spectra. Values of the chemical shifts, multiplicity and integrated intensity of 1 H and 13C signals in one-dimensional NMR spectra were defined. Homo- and heteronuclear interactions confirming structure of the investigated compounds were determined with (1 H-1 H) COSY and (1 H-13C) HMQC spectra. Data on an antiradical activity of synthesized 6-methyl-4-oxo-4H-chromen-3-acylhydrazones were showed. It was shown that the above compounds in the final concentration of 50 µM reduce the optical density of the initial solution of the DPPG radical by 27.5%, 25.2% and 8.8%, respectively, therefore, do not show pronounced antiradical activity under the conditions of this test system.